(untitled) (JURDIKSCA: Jurnal Pendidikan Agama Hindu Mahasiswa Pascasarjana, 2025)
ABSTRACT This research focuses on developing an E-Module with Edutainment features centered on the Chess Boarding stages for teaching Hindu Religion and Character in fourth-grade elementary school. The objectives include assessing the practicality and validity of this EModule and evaluating its effectiveness in improving learning outcomes. The study involved 28 fourth-grade students, a subject teacher, two language experts, two educational media experts, and two Hindu religious educational material experts. Data collection utilized practicality and validity questionnaires, analyzed using one-sample t-test and percentage calculations. The findings indicate that the developed E-Module, aimed at teaching Hindu Religious Education and Character with Edutainment elements aligned with Catur Aúrama stages, is accessible online to fourth-grade students. The module received high validity scores from experts across different categories, demonstrating its practicality and effectiveness in enhancing learning outcomes for Hindu Religion and Character in the fourth grade of SD Negeri 1 Banjar Jawa.